A survey of blockchain applications in the FinTech sector - Tara Renduchintala; Haneen Alfauri; Zebo Yang; Roberto Di Pietro; Raj Jain (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
FinTech has proven its true potential in traditional financial offerings by delivering digital financial services to individuals worldwide. The pandemic has accelerated how people interact with financial services and has resulted in long-term changes to societies and economies. FinTech has expanded access to financial services and has made such changes possible. FinTech or Financial Technology refers to using new technologies for financial services. Artificial Intelligence, Blockchain, and cloud computing are a few technologies currently being applied to FinTech. In this paper, we consider FinTech, which partly uses blockchain technology. Blockchain technology plays a vital role in the financial sector as it ultimately lifts trust and the need for third-party verification by using consensus-based verification. This survey provides a comprehensive summary of the most relevant blockchain-based FinTech implementations and an overview of FinTech sectors and segments. For each segment, we provide a critique and a discussion on how each blockchain implementation contributes to solving the majority of problems faced by FinTech companies and researchers. This research aims to direct the future of financial solutions by providing an outline of the applications of blockchain technology and distributed ledger technology (DLT) for FinTech. We discuss various implementations, limitations, and challenges of blockchain-based FinTech applications. We conclude this work by exploring possible strengths, weaknesses, opportunities, and threats (SWOT) analysis and future research directions.
Keywords: 650; bitcoin; blockchain; deposits and lending; digital wallet; Ethereum; financial services; FinTech; Hyperledger; payment services; smart contract